Light, sound & electricity - Rogers, Kirsteen; Bhachu, Verinder; Howell, Laura; Kirkby, Joanne (Tulsa, Okla. : EDC, 2002)
An introduction to the world of physics, focusing on light, sound, and electricity, with explanations of related scientific terms, experiments and activities, study guides, and links to over one hundred related Web sites.
Includes index.
6.1
3-6
Keywords: Electromagnetic waves -- Juvenile literature; Light -- Juvenile literature; Sound -- Juvenile literature; Electricity; Light; Sound; Electricity; Light; Sound